Answer:
(6, 2)
Step-by-step explanation:
Given the 2 equations
2x - y = 10 → (1)
y = [tex]\frac{1}{2}[/tex] x + 5 → (2)
Substitute y = - [tex]\frac{1}{2}[/tex] x + 5 into (1)
2x - (- [tex]\frac{1}{2}[/tex] x + 5) = 10
2x + [tex]\frac{1}{2}[/tex] x - 5 = 10
[tex]\frac{5}{2}[/tex] x - 5 = 10 ( add 5 to both sides )
[tex]\frac{5}{2}[/tex] x = 15
Multiply both sides by 2 and divide by 5
5x = 30 ⇒ x = 6
Substitute x = 6 into (1)
12 - y = 10 ( subtract 12 from both sides )
- y = - 2 ( multiply both sides by - 1 )
y = 2
Solution is (6, 2)